INOVASI DESAIN KEMASAN PRODUK & REPACKAGING PADA UMKM RENGGINANG “BU TAMSUNI” - Ratna Hardaningtyas; Helmi Artikasari (Universitas Islam Malang, 2022)
This service aims to determine the effect of product packaging on purchasing decisions in Bu Tamsuni's rengginang business. The method used in community service is through socialization, training and mentoring. After the program is implemented, the product packaging is thicker so that the product is not easily damaged and new designs are more attractive to buyers. With the implementation of the community service program, it can help Mrs. Tamsuni to increase the sales of her products.